Hubungan Status Imunisasi dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Andalas Kota Padang - Riona, Vira Harisa; Masnadi, Nice Rachmawati; Firdawati, Firdawati; Harmen, Anggia Perdana; Elmatris, Elmatris; Fadila, Zurayya (Jurnal Kesehatan Andalas, 2025)
Stunting is a linear growth failure caused by chronic malnutrition and recurrent infections that mainly occur in the first 1000 days of life. Infectious diseases can be prevented by providing immunizations. Immunization is one way to increase one's immunity against disease exposure actively. Objective: To determined the relation of immunization status with the incidence of stunting in children. Methods: Analytical research with a case-control design on 98 under-five children in the working area of Andalas Health Center was conducted from June to November 2024. Sampling was done by simple random sampling. Anthropometry was measured using body length or height measurements according to standards and data were collected by questionnaire. The data analysis used was Chi-square. Results: The incidence of stunting in the working area of Andalas Health Center was mainly (89.8%) experienced by children aged 24 - 59 months and more than half (59.2%) were female and most (81.6%) had an incomplete basic immunization status. The study also found that more than half (59.2%) of mothers' education in stunted children was high school and most (81.6%) occurred in mothers who did not work. There is a statistically significant relation between immunization status and the incidence of stunting in children, with p = 0.027 (p value <0.05) and OR value = 3.065. Conclusion: This means that under-five children who do not have complete basic immunization status have a 3.065 times higher chance of stunting than under-five children with complete basic immunization status. Keywords:  immunization status, under-five children, stunting